The Dynamics of the Labor Markets in Chile - Lima, Víctor (Estudios de Economía, 2016)
Through flows from 3 states, employment, unemployment and out of the labor force, we analyze the dynamics of labor markets in Chile from 1962-2007. We identify some periods of different labor market regimes and relate them with changes in flexibility. We found that reforms such as that of 1967, which introduced the “just cause” requirement to fire workers, did not help workers to keep their jobs, but there is no evidence of significant changes in inflexibility. Other labor regimes significantly affected transitions, but surprisingly, it was the new regime identified in 1990, that increased mobility. We interpret this as the result of the consolidation of a flexibility prone model that, until then, had been associated with an unpopular imposition by the military regime. Finally, we do not find any evidence showing that after 1998 the changes in labor participation and consequently, that the explanations of the changes in the unemployment rate could be associated with “added and discouraged worker effects.”